2019
DOI: 10.1007/s12253-019-00678-1
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of Nuclear Staining for Ki-67, p53 and Survivin as a New Prognostic Factor in Non-muscle Invasive Bladder Cancer

Abstract: The aim of the study was to determine the prognostic value of expression levels of biomarkers selected on the basis of the literature: p53, Ki-67, survivin, β-catenin, E-cadherin and N-cadherin in patients with non-muscle invasive bladder cancer. Immunohistochemistry was performed on sections of primary papillary carcinoma of the bladder removed during transurethral resection of the tumor in 134 patients. The expression of β-catenin and E-cadherin was found in all analyzed cases and Ncadherin expression was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
0
14
1
Order By: Relevance
“…Ki67 is a DNA-bound protein activated only during the proliferation phase and is not detected during cell cycle quiescence. Studies on Ki67 in UC have reported it as a prognostic factor for recurrence and progression in upper tract UC ( 19 , 42 ) NMIBC after TURB ( 43 , 44 ). In the present study, we found a correlation between higher stages of UC and increased Ki67 expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…Ki67 is a DNA-bound protein activated only during the proliferation phase and is not detected during cell cycle quiescence. Studies on Ki67 in UC have reported it as a prognostic factor for recurrence and progression in upper tract UC ( 19 , 42 ) NMIBC after TURB ( 43 , 44 ). In the present study, we found a correlation between higher stages of UC and increased Ki67 expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…Our data are consistent with most researchers’ conclusions, who also noted a correlation between the Ki-67 expression and the stage and grade of malignancy. The presence of a high Ki-67 expression might be a prognostic factor of recurrence in the near future [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrations in Ki-67 expression are associated with worse results of histopathology and clinical outcome in patients (29). Expression of Ki-67 may provide additional information that will allow more accurate stratifi cation of the risk of NMIBC recurrence after TURBT (13).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports showed that Ki-67 is an independent poor prognostic factor for NMIBC (10,11). The expression level of the Ki-67 signifi cantly correlates with recurrence rate and histopathological differentiation of the tumor (12,13).…”
Section: Introductionmentioning
confidence: 99%